Folic‐Acid‐Functionalized Au Nanoclusters with Red Fluorescence Emission for Rapid and Selective Detection of Cancer Cells. Issue 1 (5th January 2022) - Wu, Miao; Cui, Huijing; Yang, Yizhou; Dang, Ben; Li, Daowei; Zhang, Zhuqing; Yang, Xudong
Abstract: Metal nanoclusters have low toxicity and excellent fluorescence properties, and play an important role in environmental and biological detection. Herein, we demonstrate a new approach for synthesis of fluorescent Au nanoclusters (Au NCs) with the function of cancer cells detection. Firstly, we design and synthesize the copolymers of Folic acid–bovine serum albumin (FA‐BSA). In addition, the FA‐BSA copolymer prepared can be used as both stabilizer and reducer of Au NCs, and Au NCs were synthesized by simple hydrothermal method. Therefore, we obtain the fluorescent Au NCs by a convenient, safety and environment‐friendly route. The as‐prepared FA‐functionalized Au NCs are water‐soluble, highly stable and good biological compatibility, and exhibit longwave emission with red light region. Significantly, the Au NCs show outstanding capacity to specifically target the cells overexpressing the folate receptor (FR). These properties indicate that the prepared Au NCs are a promising fluorescent probe for cancer diagnosis and treatment. Abstract : We have produced a new type of red fluorescence emitting Au NCs. The as‐prepared FA‐BSA−Au NCs (FA: folic acid, BSA: bovine albumin) are water‐soluble, highly stable and good biological compatibility, and exhibit longwave emission with red light region. Significantly, the Au NCs show outstanding capacity to specifically target the cells overexpressing the folate receptor (FR). The prepared FA‐BSA−Au NCs can be used in biological imaging, cancer diagnosis and targeted drug delivery.